Hollow Palladium‐Gold Nanochains with Periodic Concave Structures as Superior ORR Electrocatalysts and Highly Efficient SERS Substrates. Issue 18 (12th March 2020) - Jiao, Wenling; Chen, Chen; You, Wenbin; Zhao, Xiaoran; Zhang, Jie; Feng, Yuzhang; Wang, Peng; Che, Renchao
Abstract: Unique palladium‐gold hollow nanochains (PdAu HCs) with 1D architecture and an ultrathin Pd‐rich skin exhibit fantastic oxygen reduction reaction (ORR) enhancements due to their high conductivity, structural stability, and maximized atomic utilization. More importantly, such PdAu HCs possess periodic concave structures that boost ORR performance. These structures readily form high‐density high‐index facets, and fewer arc edges. Concave structures can deliver strong strain effects and surface charge accumulation is revealed by off‐axis electron holography. In addition, periodic concave structures can provide strong localized surface–plasmon coupling, which means that PdAu HCs have great potential as efficient surface‐enhanced Raman scattering (SERS) substrates. This study offers a novel and general approach for the design of complex noble metal‐based nanostructures as efficient ORR catalysts and SERS substrates. Abstract : Unique palladium‐gold hollow nanochains (PdAu HCs) with periodic concave structures are synthesized via a combined magnetic‐field assisted assembly and galvanic replacement strategy. 1D porous hollow features and concave nanolayers enable PdAu HCs to be highly efficient oxygen reduction reaction (ORR) electrocatalysts and surface‐enhanced Raman scattering (SERS) substrates. Moreover, the microstructural mechanism of the enhanced ORR and SERS performances of PdAu HCs is proposed via transmission electron microscopy.